Threats of COVID-19 Reinfection: A Review of the Evidence from the Literature - Adnan, Muhammad Luthfi; Fauziyati, Ana (Jurnal Penyakit Dalam Indonesia, 2022)
Case of COVID-19 reinfection are related to immune factors in patients who have recovered by the natural course of the infecting pathogen. However, the chance of COVID-19 reinfection are still not well established. This review aimed to discuss about reinfection-related studies, including causes and clinical manifestations, and reinfection management. Reinfection happens when a patient is infected by the SARS-CoV-2 virus, which has a different genome from previous infection. Although the comparison of clinical manifestation between reinfection and the previous infection is not clear, it is believed that vulnerable populations may have worse outcomes. Vaccination is the main option to reduce the severity of reinfection. Further studies are needed to understand the mechanisms and management of COVID-19 reinfection. Thus, the development of COVID-19 treatment and vaccine can be more effective.